Enhancing Quality of Learning Experiences for Students with Disabilities in Higher Education Institutions in Alignment with Sustainable Development Goals - Nassar, Farid Saber; Abbas, Ahmed Osman; Al-Sify, Hassan (Journal of Ecohumanism, 2024)
Enhancing learning experiences for students with disabilities in higher education is essential for achieving the Sustainable Development Goals (SDGs) related to inclusive and equitable education. This study aims to ascertain the principal elements that enhance the quality of experiential learning for Students with Disabilities (SWD) at higher education institutions (HEIs) in accordance with SDGs. This study utilizes a qualitative descriptive research technique, focusing on the examination of critical aspects that might enhance the learning experience for students with disabilities at HEIs in alignment with the SDGs. The findings indicated that although several HEIs have enacted policies to enhance accessibility for SWD, considerable obstacles persist in the domains of assistive technology integration, curricular adaptability, and faculty development. The current study focuses on positive examples of how institutions have linked their projects to the SDGs. One way they have done this is by using flexible technology, teaching methods that include everyone, and strong support networks for institutions, to enhance the quality of learning experiences for SWD in university life and to fully utilize their potential in global national development initiatives.